Perspectives and challenges in the High School Reform - Law 13.415/2017: problematizations from the preparatory stages for the National Popular Summit of Education (CONAPE-2022) (Olhar de Professor, 2023)
This article analyzes the implementation of the High School Reform, Law n. 13,415/2017, its effects and resistances. The research took the Foucaultian concept of Governmentality and the Base Document for the National Popular Conference on Education (2022). The archeology was assumed as methodology with a documental research design and the observation as technique. The analysis evidenced that the implementation of new devices for the last stage of High School, led the state of South Mato Grosso (MS) establish the Law n. 4.973/2016, creating the Program Escola da Autoria, as response from the Program for Fostering Full-Time Schools and to the alteration of curricula of Secondary Education. It is concluded that new net of relations of powers and knowledges emerged from the proposition of new practices, related to the student/author model of learning as well as their Life Project, being the Escola de Autoria one of them.
Keywords: High school reform. BNCC. Educative Policies.